Multifocal Aeromonas Osteomyelitis in a Child with Leukemia. (21st April 2016) - Doganis, Dimitrios; Baka, Margarita; Tsolia, Maria; Pourtsidis, Apostolos; Lebessi, Evangelia; Varvoutsi, Maria; Bouhoutsou, Despina; Kosmidis, Helen
Abstract : Aeromonas hydrophila is a Gram negative organism causing both intestinal and extraintestinal disease. The case of a 14-year-old girl with underlying immunodeficiency and leukemia who developed systemic A. hydrophila infection is described in this report. While in deep bone marrow aplasia she developed fever, severe pain in the lower extremities, and swelling of the left femur. Blood culture showed Escherichia coli and A. hydrophila whereas pus culture from the soft tissue swelling showed the presence of A. hydrophila . Imaging studies showed diffuse osteolytic lesions. Patient received 5 months of intravenous and oral antibiotics and she improved clinically whereas the radiology findings persisted.